Authorship, Collaboration, and Funding Trends in Implantology Literature: Analysis of Five Journals From 2005 to 2009 - Ricardo Barao, Valentim Adelino [UNESP]; Shyamsunder, Nodesh; Yuan, Judy Chia-Chun; Lee, Damian J.; Assunção, Wirley Goncalves [UNESP]; Sukotjo, Cortino (Lippincott Williams & Wilkins, 2011)
Purpose: To identify the trend of authorship in dental implant by exploring the prevalence of coauthored articles and to investigate the collaboration efforts, trends in funding involved in original articles, and their relationships. Materials: Articles published in the Clinical Oral Implants Research, International Journal of Oral & Maxillofacial Implants, Clinical Implant Dentistry and Related Research, Implant Dentistry, and Journal of Oral Implantology from 2005 to 2009 were reviewed. Nonoriginal articles were excluded. For each included articles, number of authors, collaboration efforts, and extramural funding were recorded. Descriptive and analytical statistics (alpha = 0.05), including logistic regression analysis and chi(2) test, were used. Results: From a total of 2085 articles, 1503 met the inclusion criteria. Publications with 5 or more authors increased over time (P = 0.813). The amount of collaboration among different disciplines, institutions, and countries all increased. The greatest increase of collaboration was seen among institutions (P = 0.09). Non-funding studies decreased over time (P = 0.031). There was a strong association between collaboration and funding for the manuscripts during the years studied (OR, 1.5). Conclusion: The number of authors per articles and collaborative studies increased over time in implant-related journals. Collaborative studies were more likely to be funded. (Implant Dent 2011;20:68-75)
Keywords: authorship; collaboration; funding; implant; original articles